Exploring the Efficacy of “Mufradat Astronaut” Learning Media in Enhancing Arabic Vocabulary Proficiency: A Case Study of Second-grade Students at MI Khadijah Malang - Mi'ratussalamah; Nur Anisah Ridwan Ridwan; Muhammad Lukman Arifinto; Saja Jamal Ibrahim Hamdan (PPPBA, 2024)
The effectiveness of educational tools in enhancing learning outcomes is a crucial area of exploration in pedagogical research. This study focuses on evaluating the impact of Mufradat Astronaut learning media, a novel pictorial learning tool designed to integrate learning with play, on the proficiency levels of second-grade students at MI Khadijah Malang. Drawing from Kurt Lewin's theory of Classroom Action Research, the research employs a systematic approach encompassing planning, action, observation, and reflection phases. Through the integration of mufradat images onto the Mufradat Astronaut prism board, aligned with the curriculum, this study investigates the extent to which the utilization of Mufradat Astronaut media contributes to enhanced mufradat mastery among students. The findings reveal a significant improvement, with a remarkable 50.05% increase in mufradat mastery observed from pre-cycle to cycle III. This research underscores the transformative potential of Mufradat Astronaut media as an engaging and effective alternative learning medium. Beyond its immediate impact on student proficiency, the study advocates for fostering a culture of innovation among educators, encouraging the adoption of dynamic and enjoyable teaching methodologies to facilitate deeper student understanding.